Phenomena by Annie Jacobson - McMoneagle, Joe (Journal of Scientific Exploration, 2017)
The book opens with a concise statement within the PROLOGUE, stating what the book is about. It’s about: “The U.S. government’s decades-long interest in anomalous mental phenomena, including extra-sensory perception [ESP], psychokinesis [PK], map dowsing, and other forms of divination, . . .” True. “And then, just a few years after the end of World War II, the U.S. government determined anomalous mental phenomena to be effective military and intelligence tools, and began to investigate their possible use in classified operations.” Not true. Jacobson, then jumps up to 1972, and addresses what is essentially the beginning of what she calls “The real action began in 1972, when a small group of promising young scientists was approached by the Central Intelligence Agency to embark upon a research program involving psychics, or “sensitives.” At; “Stanford Research Institute . . .” All of which is somewhat true. The CIA did spend fifty-thousand dollars to ascertain if ESP could be of value and it was determined that it could be. Jacobson states because of this finding, “. . . everybody wanted in on it – the Navy, the Air Force, the Army [Including its Intelligence and Security Command and the Development and Readiness Command], the Coast Guard . . .” and she goes on to list just about all the people who were eventually supported by Project Star Gate. She cleverly twists the truth here to imply that the entire U.S. Government wanted in on it, which was – not true. The entire reason the US Army, specifically the 902nd MI Group, Fort George G. Meade, Maryland originally became involved, was based on the premise that if what was happening at SRI-International was true, then perhaps what the Soviets were doing in the field of the Paranormal could be a threat to the security of the United States. After nearly a year of investigating if this might be true, the 902nd MI, made the decision to find three possible psychics within its ranks, spend a year training them to do what was being done at SRI, then use them to target our own facilities, after which an independent analysis of the material would be made to verify what the actual threat to the United States from the Soviet Union might be. It was called Project Gondola Wish.